INOVASI PENGENDALIAN LALAT BUAH PADA PENGEMBANGAN AGROWISATA JAMBU KRISTAL DI LAHAN GAMBUT - Melhanah; Wijantri Kusumadati; Rahmawati Budi Mulyani; Adrianson Agus Djaya; Riky Nur Rohman; Prida (BPFP Universitas Bengkulu, 2026)
[FRUIT FLY CONTROL INNOVATION FOR CRYSTAL GUAVA AGROTOURISM DEVELOPMENT ON PEATLANDS]. Sebangau District, Palangka Raya City, is developing agrotourism for picking crystal guava (Psidium guajava L. var. ‘Crystal’) on peatlands, but attacks by fruit flies of the genus Bactrocera spp. have caused crop losses of up to 40-60% globally. This study aims to evaluate the effectiveness of combined attractants to attract male and female fruit flies and measure their impact on the quality of crystal guava fruit. The study was conducted in two stages on four farmers' fields (2024). Stage I: collection of fruit flies using Steiner traps with three attractants: methyl eugenol (ME), processed cocoa waste with preservatives (PCWWP), and mango extract (MGE), each with 20 replicates/location, 4 weeks. Stage II: fruit quality testing (vitamin C content, reducible sugar, hardness, crispness, organoleptic test of 20 panelists) from the best trap-protected plants. The results showed that 31,759 fruit flies were trapped, dominated by Bactrocera carambolae (98.53%), B. umbrosa (1.34%), and B. cucurbitae (0.13%). The ME+PCWWP combination was the most effective (p<0.01), capturing 99.84% of the male population including 0.16% of the females. Fruit from this treatment had the highest vitamin C (153.6 mg/100g), reducible sugar (9.9°Brix), best organoleptic preferences for hardness (5.2), crispness (4.8), taste (6.1), and overall (scale 5.9/6). Female B. cucurbitae were more attracted to ME+MGE (ratio 1:5). The combination of ME+OLK is recommended for sustainable fruit fly control in peatland crystal guava agrotourism, improving fruit quality and tourist attraction.